Client-centred practice in occupational therapy: Critical reflections. (May 2013) - Whalley Hammell, Karen R.
Abstract Aims: The occupational therapy profession has long proclaimed its commitment to a client-centred philosophy of practice and the assumption that occupational therapists consistently practice in a client-centred manner has become central to the profession's self-image and public rhetoric. However, client-centred practice has been subjected to little critical reflection within the occupational therapy profession. The aim of this paper is to foster critical reflection concerning the authenticity and veracity of the profession's commitment to client-centred practices. Major findings: Client-centred practice is defined without evident reference to clients' perspectives. Few occupational therapy researchers have sought clients' perceptions of the client-centred nature of their occupational therapy services. Occupational therapy research is neither consistently undertaken in a collaborative manner, nor are the profession's theories developed through explicit reference to a diversity of clients' perspectives. Professional practices and service evaluations do not consistently seek clients' viewpoints. Client-centred rhetoric is politically expedient and may be a professionalizing strategy employed to increase status and entrench power. Practice conclusion: Although exemplary client-centred occupational therapy practices exist, evidence suggests that the profession does not adhere consistently to its espoused client-centred principle in all its practices. The client-centred practice of occupational therapy should be subjected to assiduous critical reflection.